2021
DOI: 10.1371/journal.pone.0259047
|View full text |Cite
|
Sign up to set email alerts
|

Stroke risk associated with NSAIDs uses in women with dysmenorrhea: A population-based cohort study

Abstract: Objective Dysmenorrhea is among the most common type of gynecological problem, affecting young women across the globe. This study assessed the comparative risk of stroke associated with the use of nonsteroidal anti-inflammatory drugs (NSAIDs) and non-NSAIDs in women with dysmenorrhea while taking into account the following factors such as age, history of pregnancy, NSAIDs uses and its duration of use, and selected comorbidities. Methodology We used a quantitative research approach based on a comparative case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The aHR for nonsteroidal anti-inflammatory drug use was 1.47 (95% CI, 0.93–2.32). 143 The aHR for nonsteroidal anti-inflammatory drug use ≥24 d/mo was 2.29 (95% CI, 1.36–3.84).…”
Section: Stroke (Cerebrovascular Diseases)mentioning
confidence: 98%
“…The aHR for nonsteroidal anti-inflammatory drug use was 1.47 (95% CI, 0.93–2.32). 143 The aHR for nonsteroidal anti-inflammatory drug use ≥24 d/mo was 2.29 (95% CI, 1.36–3.84).…”
Section: Stroke (Cerebrovascular Diseases)mentioning
confidence: 98%
“…The aHR for nonsteroidal anti-inflammatory drug use was 1.47 (95% CI, 0.93–2.32). 124 The aHR for nonsteroidal anti-inflammatory drug use ≥24 d/mo was 2.29 (95% CI, 1.36–3.84).…”
Section: Stroke (Cerebrovascular Diseases)mentioning
confidence: 98%
“…A recent study examining the risk of stroke associated with NSAID uses for dysmenorrhea found that patients who took the medicine for 13 or more days per month were at an elevated risk of stroke. Those taking NSAIDs less than 13 days per month were at a lower risk of stroke with an aHR of 0.51 (95% CI 0.13–2.10) [ 42 ]. However, very few women had been prescribed NSAIDs for more than 10 days during the period with PD in this study.…”
Section: Discussionmentioning
confidence: 99%